Effect of Modified Rubber Particles Mixing Amount on Properties of Cement Mortar - Gang Xue; Mei-ling Cao (Advances in Civil Engineering)
The crumb rubber cement mortar is prepared by the crumb rubber aggregates in 60 mesh which are modified by 1% polyvinyl alcohol (PVA) solution. Some mechanical properties of cement mortar with different crumb rubber aggregate amounts are researched including compressive strength, flexural strength, the ratio of compressive strength to flexural strength, impact resistance, and dry contraction percentage. In our tests, we consider six kinds of the rubber contents, 0%, 7.5%, 15%, 19%, 22.5%, and 30%, respectively. The optimal mixing amount of crumb rubber is determined by measuring three indices, the ratio of compressive strength to flexural strength, impact resistance, and dry contraction percentage. It is shown by test that the ratio of compressive strength to flexural strength is the smallest when the mixing amount of rubber is 19%; meanwhile high impact resistance and rational drying shrinkage are observed. The optimal mixing amount of the rubber particles is 19% determined by this test.